Konseling Kelompok dengan Pendekatan Cognitive Behavior Therapy (CBT) untuk Meningkatkan Kesadaran Pendidikan - Sulistianingsih, Sulistianingsih; Widiantari, Dian (Coution: Journal Counseling and Education, 2020)
This study discusses group counseling using one of the counseling approaches namely cognitive behavior therapy (CBT) in adolescents who do not consider education important at a higher level. The purpose of CBT is to invite clients to challenge wrong thoughts and emotions by presenting evidence that contradicts their beliefs about the problem at hand. The purpose of this article is to look at the usefulness of group counseling through cognitive behavioral therapy (CBT) approaches in an effort to increase awareness of continuing education which is higher in adolescents in Banaran village, Kulonprogo regency. Data collection is done by using methods of observation, interviews and documentation. Data analysis was performed using qualitative descriptive analysis which included data reduction, data presentation, and drawing conclusions. Keywords: Group Counseling; Cognitive Behavior Therapy; Education Awareness. Abstrak Penelitian ini membahas mengenai konseling kelompok dengan menggunakan salah satu pendekatan konseling yaitu cognitive behavior therapy (CBT) pada remaja yang kurang menganggap penting pendidikan dalam jenjang yang lebih tinggi. Tujuan CBT adalah mengajak klien untuk menentang pikiran dan emosi yang salah dengan menampilkan bukti-bukti yang bertentangan dengan keyakinan mereka tentang masalah yang dihadapi. Tujuan artikel ini adalah untuk melihat kegunaan konseling kelompok melalui pendekatan cognitive behavior therapy (CBT) dalam upaya meningkatkan kesadaran melanjutkan pendidikan yang lebih tinggi pada remaja di Dusun Banaran Kabupaten Kulonprogo. Pengumpulan data dilakukan dengan menggunakan metode observasi, wawancara dan dokumentasi. Analisis data dilakukan dengan menggunakan analisis deskriptif kualitatif yang meliputi reduksi data, penyajian data dan penarikan kesimpulan. Kata kunci: Konseling Kelompok; Cognitive Behavior Therapy; Kesadaran Pendidikan.